2013
DOI: 10.1007/s12639-013-0243-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods of Marshallagia marshalli donor sheep production

Abstract: Marshallagia marshalli is found in the abomasums of sheep, goats and wild ruminants in tropical and sub tropical climates. In Iran among different species of Ostertagiinae that can infect sheep, M. marshalli is currently the major cause of parasitic gastroenteritis in ruminant. Having a donor animal is essential for various studies. In the present study we compared the efficacy of two different method of M. marshalli donor sheep production. In the first method, M. marshalli donor sheep was produced by transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Marshallagia marshalli is the gastrointestinal helminth with the highest prevalence and infection intensity throughout Dall’s sheep distributional range[ 28 – 30 ]. It is an important cause of parasitic gastroenteritis in wild and domestic sheep[ 31 , 67 ] and can cause marked alterations in the abomasal physiology of the infected host[ 31 , 33 ]. In Dall’ sheep, this detrimental effect may occur through a variety of mechanisms that have been extensively studied for related nematodes in domestic ungulates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marshallagia marshalli is the gastrointestinal helminth with the highest prevalence and infection intensity throughout Dall’s sheep distributional range[ 28 – 30 ]. It is an important cause of parasitic gastroenteritis in wild and domestic sheep[ 31 , 67 ] and can cause marked alterations in the abomasal physiology of the infected host[ 31 , 33 ]. In Dall’ sheep, this detrimental effect may occur through a variety of mechanisms that have been extensively studied for related nematodes in domestic ungulates.…”
Section: Discussionmentioning
confidence: 99%
“…marshalli include a marked loss of functional parietal cells in the abomasum of the host resulting in an increase of abomasal pH, and an increase of both serum pepsinogen and serum gastrin concentrations[ 31 , 32 ]. The clinical presentation is similar to other gastrointestinal parasites including appetite depression, weight loss, constipation and diarrhea[ 31 , 33 ]. Based on field observations in Alaska, Neilsen and Neiland[ 29 ] suggested that M .…”
Section: Introductionmentioning
confidence: 99%
“…In last decade the infection of Marshallagia marshalli was recorded from Algeria (Meradi et al, 2011), Iran (Naem and Gorgani, 2011;Moradpour et al, 2014) and Iraq (Al-Bayati and Arsalan, 2009;Nasrullah et al, 2014;Mohammedameen, 2016). Meradi et al (2011) reported prevalence of this nematode parasite in small ruminants ranging 21 to 81 percent in Algeria and established significant linear regression between prevalence of Marshallagia marshalli and rainfall.…”
Section: Marshallagia Marshallimentioning
confidence: 99%